Household Inflation Inequality in the United States and Europe - Daniel Stempel (Credit and Capital Markets – Kredit und Kapital, 2022)
Inflation rates differ across households depending on their sociodemographic characteristics. This paper calculates the inflation rates experienced by income quintiles in the US, the EU, France, Germany, Italy, Spain, and the UK between 2001 and 2021. The results indicate substantial inflation inequality between quintiles. Households with lower income experienced higher inflation rates than households with higher income. The aggregated inflation differential between the lowest and the highest quintile is always positive, with values up to 8.56 percentage points. One reason for this inequality is differing consumption baskets of households: essential goods, which exhibited above-average inflation, are more prevalent in the consumption baskets of lower quintiles, while non-essentials, which exhibited below-average inflation, are more relevant for higher quintiles. Upon examining inflation inequality across quintiles between January and June 2022, a similar pattern emerged in Europe. In the US, however, higher income quintiles experienced higher inflation rates in each month of 2022.
Keywords: D12; D31; E31; 330; Inflation Inequality; Household Heterogeneity; Inflation Differentials